Host Differences Affecting Resistance and Susceptibility of the Second Generation of a Pekin Duck Flock to Duck Hepatitis A Virus Genotype 3 - Wang, Xiaoyan; Zhang, Jiaojiao; Meng, Runze; Jiang, Yong; Liang, Suyun; Zhang, Yunsheng; Xie, Ming; Zhou, Zhengkui; Hou, Shuisheng (Frontiers in Microbiology, 2017)
Earlier work suggested the possibility to anti duck hepatitis A virus genotype 3 (DHAV-3) using the resistance breeding strategy. Here, we report the creation of the second generations of a resistant Pekin duck flock (designated Z8R2) and a highly susceptible Pekin duck flock (designated Z8S2) and the investigation of their responses to DHAV-3. Experimental infection with DHAV-3 at 7 days of age resulted in a high mortality (66.3%) in 11 susceptible Z8S2 families and an extremely low mortality rate (2.67%) in 32 Z8R2 families, indicating that Z8R2 exhibits strong resistance to DHAV-3, while Z8S2 is highly susceptible to the virus. Detection of DHAV-3 in the liver between 1 and 60 hours post inoculation (hpi) suggests that DHAV-3 can be replicated rapidly and efficiently in the liver of Z8S2, whereas the replication of the virus in the liver of Z8R2 is suppressed greatly. High levels of serum biochemical markers (e.g., ALT, AST, ALP and GGT) were detected in Z8S2 at 24 hpi, which were significantly higher than those in Z8R2. Analysis of transcripts in the liver revealed that the expression levels of several pattern recognition receptors (PRRs) (e.g., TLR4/7, RIG-1 and MDA5) and cytokines (e.g., IL-2, IL-6, IL-8, IFN-α, and IFN-γ) in Z8S2 were significantly higher than those in Z8R2 at 12 and 24 hpi. Together these findings suggest that Z8R2 and Z8S2 Pekin ducks, which were derived from the same Z8 line, exhibit disparate pathogenic outcomes following DHAV-3 infection. Therefore, it is possible to select a Pekin duck flock resistant to DHAV-3 employing the strategy described here. It is likely that the high viral load and the strong inflammatory response correlate with the high susceptibility of Z8S2 Pekin ducks to DHAV-3.